An auto-incrementing nanosecond delay circuit - Jang, H. U.; Blieck, J.; Veshapidze, G.; Trachy, M. L.; DePaola, B. D. (My University, 2007)
We describe a circuit that acts as an auto-incrementing delay. The circuit allows the user to adjust the total number of delays in a cycle, the incremental delay value, and the amount of time that is spent at each delay step. The circuit is stand-alone, yet is readily interfaced to data acquisition systems. Depending on the delay chip used and the number of steps required, the delay step can be as short as 250 ps or as long as 640 ns. The circuit has been used to control the temporal separation between pulses from independent lasers. This was instrumental in our measurement of population dynamics in an optically excited three-level ladder system.